Sex, Rhythm & Death: The effect of sexual activity on cardiac arrhythmias and sudden cardiac death - Dye, Cicely Anne; Engelstein, Erica; Swearingen, Sean; Murphy, Jeanine; Larsen, Timothy; Volgman, Annabelle Santos (Frontiers in Cardiovascular Medicine, 2022)
Arrhythmias and sudden cardiac death with sexual activity are rare. However, the demographics are changing regarding the cardiovascular patients at risk for these events. Recent studies have highlighted that the individuals having cardiac events during sexual activity are becoming younger, with a higher proportion of female decedents than previously described. There needs to be an open dialog between the cardiovascular team and the cardiac patient to provide the education and reassurance necessary for cardiovascular patients to participate in sexual intercourse safely. This paper reviews how sexual activity can lead to an increase in cardiac arrhythmias and sudden cardiac arrest in patients that are not medically optimized or are unaware of their underlying cardiac condition. The most common cardiovascular diseases associated with sexually induced arrhythmias and arrest are discussed regarding their potential risk and the psychosocial impact of this risk on these patients. Finally, cardiovascular medications and implantable cardioverter-defibrillators (ICDs) are addressed by reviewing the literature on the safety profile of these cardiac interventions in this patient population. Overall, sexual activity is safe for most cardiac patients, and providing proper education to the patient and their partner can improve the safety profile for patients with higher risk cardiovascular conditions. To give the appropriate education and reassurance necessary, cardiovascular team members need an understanding of the pathophysiology of how sexual activity can provoke arrhythmias and sudden cardiac arrest. Healthcare providers also need to build comfort in speaking to all patients and ensure that sexual partners, female patients, and those in the LGBTQIA + community receive the same access to counseling but tailored to their individual needs.